Anaerobic granular sludge-derived activated carbon: preparation, characterization and superior dye adsorption capacity. Issue 38 (14th August 2016) - Zhang, Ge; Yan, Tao; Wei, Dong; Yan, Liangguo; Wang, Xiaodong; Wei, Qin; Du, Bin
Abstract: Anaerobic granular sludge-derived activated carbon (AGSC) was prepared as a novel adsorbent for the removal of malachite green (MG) from aqueous solution. The composition and structure of AGSC were characterized by Fourier transform infrared spectroscopy, N2 adsorption–desorption isotherms, Scanning electron microscope, Zeta potential, and X-ray photoelectron spectroscopy. Adsorption capacity of MG onto AGSC was investigated in a batch system by considering the effects of various parameters including pH value, adsorbent dose, contact time, and temperature. AGSC exhibited a high surface area (741.1 m 2 /g) and adsorption capacity (304.9 mg/g). The pseudo-second-order kinetic model and the Langmuir model could well explain the adsorption processes of AGSC. Thermodynamic parameters of the adsorption processes, such as Δ G (−2.23 kJ/mol), Δ H (5.50 kJ/mol K) and Δ S (25.8 J/mol K), were also calculated. The negative Δ G and the positive Δ H indicated that the adsorption was spontaneous and endothermic. The result of this study could provide strong evidence for the potential of adsorbent in removing pollutant from wastewater.